Self-management interventions to improve skin care for pressure ulcer prevention in people with spinal cord injuries: a systematic review protocol. Issue 1 (December 2016) - Baron, Justine; Swaine, Jillian; Presseau, J.; Aspinall, Arlene; Jaglal, Susan; White, Barry; Wolfe, Dalton; Grimshaw, Jeremy
Abstract Background Pressure ulcers are a serious, common, lifelong, and costly secondary complication of spinal cord injury (SCI). Community-dwelling people with a SCI can prevent them with appropriate skin care (i.e. pressure relieving activities, skin checks). Adherence to skin care remains suboptimal however, and self-management interventions that focus on improving this have been designed. Little is known on their content, effectiveness, or theoretical basis. The aim of the proposed systematic review is to synthesize the literature on self-management interventions to improve skin care in people with a SCI. Specific objectives are to describe these interventions in relation to their content, effectiveness, theory base, and adherence to reporting guidelines for intervention description. Methods The search strategy will combine an electronic search of nine bibliographic databases (MEDLINE, Embase, PsycInfo, CENTRAL, CINAHL, Rehabdata, CIRRIE, PEDro, ERIC) and two trial registers with a manual search of relevant reference lists. Predefined eligibility criteria will be applied in a two-phase selection process involving title and abstract screening, followed by full-text screening. A data extraction spreadsheet will be applied to included papers. Intervention content will be coded using two taxonomies (behaviour change taxonomy; PRISMS self-management support taxonomy). A validated tool (Theory Coding Scheme) and the Template for Intervention Description and Replication (TIDieR) will be used to examine theoretical basis and assess adherence to reporting guidelines for intervention description. A small number of heterogeneous studies are likely to be included in this review therefore a narrative synthesis is planned. Discussion This systematic review will help identify the gaps and priorities to guide future research activities in this area. Systematic review registration PROSPEROCRD42016033191